Fatal Nonhepatic Hyperammonemia in ICU Setting: A Rare but Serious Complication following Bariatric Surgery. (10th April 2016) - Acharya, Gyanendra; Mehra, Sunil; Patel, Ronakkumar; Frunza-Stefan, Simona; Kaur, Harmanjot
Abstract : Bariatric surgery is well established in reducing weight and improving the obesity-associated morbidity and mortality. Hyperammonemic encephalopathy following bariatric surgery is rare but highly fatal if not diagnosed in time and managed aggressively. Both macro- and micronutrients deficiencies play a role. A 42-year-old Hispanic female with a history of Roux-en-Y Gastric Bypass Procedure was brought to ED for progressive altered mental status. Physical exam was remarkable for drowsiness with Glasgow Coma Scale 11, ascites, and bilateral pedal edema. Labs showed elevated ammonia, low hemoglobin, low serum prealbumin, albumin, HDL, and positive toxicology. She remained obtunded despite the treatment with Narcan and flumazenil and the serum ammonia level fluctuated despite standard treatment with lactulose and rifaximin. Laboratory investigations helped to elucidate the etiology of the hyperammonemia most likely secondary to unmasking the functional deficiency of the urea cycle enzymes. Hyperammonemia in the context of normal liver function tests becomes diagnostically challenging for physicians. Severe hyperammonemia is highly fatal. Early diagnosis and aggressive treatment can alter the prognosis favorably.